2014
DOI: 10.5935/0004-2749.20140007
|View full text |Cite
|
Sign up to set email alerts
|

Translation and validation of Convergence Insufficiency Symptom Survey (CISS) to Portuguese - psychometric results

Abstract: Projecto n o CE-FCS-2012-027 -Faculdade Ciências da Saúde -UBI. ABSTRACTPurpose: Translate and adapt the Convergence Insuficiency Symptom Survey (CISS) questionnaire to the Portuguese language and culture and assess the psychometric properties of the translated questionnaire (CISSvp). Methods: The CISS questionnaire was adapted according to the methodology recommended by some authors. The process involved two translations and backtranslations performed by independent evaluators, evaluation of these versions, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Our CISS VE showed a mean score (15.10 ± 10.13) that was comparable to those reported in studies conducted in similar populations, such as the adolescents assessed by Horan et al 6 (16.3 ± 11.4) and the university students used to develop the Portuguese version (CISS VP ; 15.56 ± 8.86). 5 These two studies provided mean scores for the entire group of participants instead of separating scores according to subjects' visual problems. Furthermore, the mean score obtained in our sample (from a general population) is higher than those reported by Rouse et al 2,38 in adults and children with normal binocular vision recruited from a clinical population (11.3 ± 8.1 for adults and 10.4 ± 8.1 for children).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our CISS VE showed a mean score (15.10 ± 10.13) that was comparable to those reported in studies conducted in similar populations, such as the adolescents assessed by Horan et al 6 (16.3 ± 11.4) and the university students used to develop the Portuguese version (CISS VP ; 15.56 ± 8.86). 5 These two studies provided mean scores for the entire group of participants instead of separating scores according to subjects' visual problems. Furthermore, the mean score obtained in our sample (from a general population) is higher than those reported by Rouse et al 2,38 in adults and children with normal binocular vision recruited from a clinical population (11.3 ± 8.1 for adults and 10.4 ± 8.1 for children).…”
Section: Discussionmentioning
confidence: 99%
“…The CISS is not a condition-specific instrument for convergence insufficiency; rather, it is useful for measuring the symptoms associated with visual discomfort caused by different factors. Accordingly, it considers the most common symptoms regarding near-vision problems 5 and provides similar scores in children with accommodative insufficiency and convergence insufficiency. 4 In addition, as described by Horan et al, 6 some patients with normal sensorimotor exam results were found to score high (i.e., showed a higher level of the assessed symptoms) on the CISS, while others with convergence insufficiency had relatively low scores.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers from the CITT group (Convergence Insufficiency Treatment Trial Investigator Group) have quantified the symptoms reported by patients with a questionnaire developed for this purpose, the CISS (Convergence Insufficiency Symptom Survey). This questionnaire has been validated for various populations, for different age-groups [1114] and has been used regularly to help with diagnosis and to assess the effectiveness in treating the syndrome [46].…”
Section: Introductionmentioning
confidence: 99%
“…The tool used to study the level of symptoms of the participants was the Portuguese version of the CISS questionnaire adapted from the original developed by the Convergence Insufficiency Treatment Trial group (CITT) [19]. This questionnaire is organized in 15 items in a Likert frequency scale, ranging from 0 (never) to 4 (always) with a total score ranging from 0 to 60.…”
Section: Ciss Questionnairementioning
confidence: 99%